Object-Oriented Software Engineering with C++ - Darrel Ince (Mcgraw Hill Book Company, 1991)
This book describes how object-oriented languages and ideas can be employed throughout the software project, starting at requirements analysis and finishing at acceptance testing. Preface, Introduction, Object-Oriented Programming, An Objected-Oriented Approach to Software Development, Modelling Data, Validating the Data Model, Abstract Data Types, The Basic Facilities of C++, Object-Oriented Programming in C++, Implementing Objects, Specifying Functionality, Putting it All Together, Software Prototyping, The Whole Process, Case Study, Index.